Research Note: ERDB Research, Development and Extension Strategies for the Production of High Quality Planting Materials - Cadiz, Rafael; Landicho, Marilyn; Aparente, Mylene (Annals of Tropical Research, 2010)
The Ecosystems Research and Development Bureau is presently conducting research, development and extension strategies for the production of high quality planting materials. The activities include the verification and assessment of existing seed stands and identification o new stands, as seed sources of indigenous and exotic species nationwide. Propagation protocols are being developed for some demand-driven indigenous species, and provenance cum progeny trials are being conducted for narra (Pterocarpus indicus), yemane (Gmelina arborea) and molave (Vitex parviflora). Extension activities include the establishment of a database of the information gathered by the project, capacity building, and production of brochures, leaflets and videos. It is considered that all possible mechanisms should be employed to transfer the research results effectively.